Stock price fragility - Greenwood, Robin; Thesmar, David (Journal of Financial Economics, 2011)
We study the relation between the ownership structure of financial assets and non-fundamental risk. We define an asset to be fragile if it is susceptible to non-fundamental shifts in demand. An asset can be fragile because of concentrated ownership, or because its owners face correlated or volatile liquidity shocks, i.e., they must buy or sell at the same time. We formalize this idea and apply it to mutual fund ownership of US stocks. Consistent with our predictions, fragility strongly predicts price volatility. We then extend the logic of fragility to investigate two natural extensions: (1) the forecast of stock return comovement and (2) the potentially destabilizing impact of arbitrageurs on stock prices.